A deixis analysis of “Die with a Smile” by Bruno Mars and Lady Gaga - Sabtiana, Rela (Universitas Islam Malang, 2025)
Deixis, a fundamental linguistic concept, refers to expressions whose meanings depend on context, including personal pronouns, temporal markers, spatial indicators, and demonstratives. While deixis has been widely studied in conversational and literary discourse, its role in song lyrics remains underexplored, particularly in shaping emotional resonance and thematic depth. This study addresses this gap by analyzing the use of deixis in Die with a Smile by Bruno Mars and Lady Gaga, focusing on how deictic expressions contribute to narrative construction and listener engagement. Employing a qualitative approach, the study identifies and categorizes deictic expressions in the lyrics, revealing that personal deixis is the most dominant (64.20%), followed by spatial deixis (18.52%), temporal deixis (13.58%), and demonstrative deixis (3.70%). Personal deixis fosters intimacy and relatability, while spatial and temporal deixis situate the narrative within emotional and situational contexts. Demonstrative deixis reinforces shared references and directs the listener’s focus. These deictic elements effectively convey themes of love, longing, and transcendence, demonstrating the intricate relationship between language, meaning, and audience perception in contemporary music. This study contributes to linguistic and musical analysis by highlighting the interplay between deixis and emotional expression in song lyrics.